2018
DOI: 10.1002/1873-3468.13084
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of telomerase reverse transcriptase hTERT in cancer stemness and metastasis

Abstract: Maintenance of chromosomal telomere length is a hallmark of cancer cells and a prerequisite for stemness. In 85-90% of all human cancers, telomere length maintenance is achieved by reactivation of telomerase, whereas in the remaining 10-15% cancers, alternative lengthening of telomeres (ALT) is observed. Reactivation of telomerase occurs by various mechanisms, one of which is accumulation of point mutations in the promoter region of the gene encoding the protein subunit hTERT. There are numerous studies linkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 42 publications
1
64
0
2
Order By: Relevance
“…Telomerelengthening, with consequent replicative immortality has been characterised as a prerequisite for oncogenesis, with TERT-mediated telomere lengthening being identified as a Cluster of differentiation 133 0.149 0.172 86 (23) factor in 85-90% of cancers types, with alternative pathways accounting for the remainder (43). However, recent evidence has suggested that in addition to telomere lengthening, TERT may have a role in endothelial-mesenchymal transformation, as well as in the induction of stemness (44,45). Classically, it was believed that tumours consisted of uniformly neoplastic cells capable of proliferating independently, and giving rise to new clonal lineages which may contribute to the emergence of therapeutic resistance or to relapse of the disease after the end of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerelengthening, with consequent replicative immortality has been characterised as a prerequisite for oncogenesis, with TERT-mediated telomere lengthening being identified as a Cluster of differentiation 133 0.149 0.172 86 (23) factor in 85-90% of cancers types, with alternative pathways accounting for the remainder (43). However, recent evidence has suggested that in addition to telomere lengthening, TERT may have a role in endothelial-mesenchymal transformation, as well as in the induction of stemness (44,45). Classically, it was believed that tumours consisted of uniformly neoplastic cells capable of proliferating independently, and giving rise to new clonal lineages which may contribute to the emergence of therapeutic resistance or to relapse of the disease after the end of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors promoting the high radioresistance of CSCs is their lower proliferative activity as compared with non-stem cancer cells; being a product of EMT, a part of the CSC pool may transiently be in a state of quiescence (see above) that makes them more radioresistant. The high telomerase activity in CSCs [3,11] may help them to escape from post-radiation replicative senescence. Moreover, CSCs have improved DNA damage response mechanisms that include the expression of Snail, excision repair cross-complementation group 1 (ERCC1) and nibrin or NBS1 -proteins assisting DNA repair in CSCs after ionizing radiation or genotoxic drug exposures (see [3] for a review).…”
Section: Resistance Of Cscs To Therapeutics Immune Attack and Stresmentioning
confidence: 99%
“…Among the cancer-promoting HSP90 client proteins, there are surely some contributing to cancer cell stemness development or responsible for the manifestation of certain qualities of CSCs. For example, it is long known that telomerase (hTERT), a telomere end-restoring enzyme, which confers a capacity for endless mitotic division without replicative senescence [11]; survivin, an antiapoptotic protein contributing to the chemo-and radioresistance of CSCs [31]; HIF1α, a transcription factor involved in hypoxia-responsive signaling, which induces EMT and CSC niche formation and also chemo-and radioresistance of CSCs [2][3][4][5]17] MMP2, MMP9, and uPA, secretory proteinases assisting CSCs to migrate through the extracellular matrix and invade the vasculature for metastasis dissemination [16]; and EGFR, Akt, and Src, components of signal pathways resulting in the improved survival and higher motility of CSCs [2][3][4][5]17] are all HSP90 client proteins [50,57,62]. Lee et al showed that the expression of HSP90α (HSPC2 [41]) was enhanced in human breast CSC-like cells enriched with ALDH while geldanamycin (an inhibitor of the HSP90 activity) was able to reduce the pool of such ALDH+ cells [63].…”
Section: Intracellular Hsp90 and Some Of Its Partners In Chaperoningmentioning
confidence: 99%
“…It has been reported that lncRNA could participate in the initiating and the progress of diseases by interfering with transcription, translation, epigenetic inheritance and some basic process of cell life activities [3]. Previous researches have demonstrated that lncRNAs play a significant role in various types of tumour [4][5][6][7], especially in lung adenocarcinoma [8][9][10]. For example, White and his colleagues characterized the lncRNA landscape in lung cancer and discovered 111 differentially expressed lncRNAs, which were termed as lung cancer-associated lncRNAs (LCALs).…”
Section: Introductionmentioning
confidence: 99%